Synthesis and electrochemical properties of porphyrazines with annulated 1,4-dithiaheterocycles - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
Porphyrazines (M=H, Mg, Zn or Cu) with 2,3-trimethyleneoxy-2,3-dihydro-1,4-dithiin or 2-ethoxy-2,3-dihydro-1,4-dithiin groups fused to each pyrrol unit have been synthesised starting with the corresponding unsaturated dicarbonitrile derivative. The elemental analysis and IR, H-1 NMR, UV-Vis and mass spectral data have been used to characterise the new compounds. Electrochemical investigations have shown that metal insertion into the porphyrazine core and substituents having high electron donating ability shift the ring centred reduction processes towards negative potentials. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: porphyrazines; phthalocyanines; magnesium; copper; zinc; electrochemistry; DISODIUM DIMERCAPTOMALEONITRILE; CRYSTAL-STRUCTURE; COMPLEXES; THIACYANOCARBONS; OXIDATION; PRODUCTS